2014
DOI: 10.1016/j.ijid.2014.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Viral genome and antiviral drug sensitivity analysis of two patients from a family cluster caused by the influenza A(H7N9) virus in Zhejiang, China, 2013

Abstract: The two patients from one family cluster were probable human-to-human transmission cases. The new isolates were sensitive to peramivir but showed reduced sensitivity to oseltamivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Among the well-described clusters of HPAI and LPAI avian influenza, it appears that the secondary cases were less severe than the index cases [9,11,12,43,44,45]. Similar to other research, the secondary deaths occurring in the H5N1 virus case clusters were markedly less severe than the index fatalities.…”
Section: Discussionsupporting
confidence: 77%
“…Among the well-described clusters of HPAI and LPAI avian influenza, it appears that the secondary cases were less severe than the index cases [9,11,12,43,44,45]. Similar to other research, the secondary deaths occurring in the H5N1 virus case clusters were markedly less severe than the index fatalities.…”
Section: Discussionsupporting
confidence: 77%
“…Reported person to person transmissions have all occurred in family clusters, suggesting that either common exposures or host genetic susceptibility might contribute to H7N9 infection. 5 6 7 8 9 10 11 12 13 Here, we report a possible person to person transmission between two unrelated individuals in a hospital, and provide epidemiological and virological evidence supportive of nosocomial infection.…”
Section: Introductionmentioning
confidence: 74%
“…Many clinical and epidemiological studies have shown that H7N9 displays obvious family aggregation, indicating that close contact between people might lead to H7N9 infection [ 15 19 ]. Once H7N9 increases its adaptability to human receptors to acquire human transmission ability, it will lead to an influenza epidemic and mass infection [ 20 ].…”
Section: Introductionmentioning
confidence: 99%